Planejamento e otimização da síntese da polianilina dopada com ácido azeláico e sua aplicação em fotodegradação - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
In the class of materials known as intrinsically conductive polymers one finds the poly aniline (PAni), which stands out for its stability at ambient conditions, its ease of synthesis, easy acquisition and low cost of the monomer. However, it has limitations related to low processability in consequence of its insolubility in most solvents, which can be improved by incorporation of functionalized acids on the polymer chain, providing improvements in its optical and electrical qualities. The conditions of synthesis directly influence the electrochemical properties, morphology, solubility and yield of synthetic polymer. A very interesting feature of conducting and semiconducting materials is their ability to act as agents in the photo catalytic degradation of organic compounds. In this context it is proposed the synthesis and characterization of the doped PAni with azelaic acid (AA),using it as ammonium persulfate (PSA) oxidizing agent, as well as the variation of some parameters of synthesis and potential applications in the photo degradation of organic compounds. In order to study the best conditions of synthesis was carried out a 23factorial design, such as using factors at the initial concentration of aniline at levels of 0.2 and 0.04 mol L-1, molar ratio acid/aniline in 1 and 1.5, furthermore synthesis system temperature of 5 and 25 degrees Celsius. In response to this was evaluated the nominal yield and the electrical conductivity. The material was examined by vibration spectroscopy in the infrared radiation sphere, termogravimetric examination, determining the electrical conductivity by the four-point method, transmission electron microscopy and X- ray diffraction. The results showed that PAni(AA) is an electrically conductive material, in the order of 10 to 3 S cm-1. The best conditions of synthesis in the studied levels were: Temperature of 5 degrees Celsius, initial Aniline concentration of 0.2 mol L-1 and molar ratio acid / aniline = 1. The amount of ethanol as co solvent showed effect on the synthesis. The made characterizations allow to affirm that the desired product was obtained. It was evaluated the photo catalytic potential of PAni(AA) and its emeraldine base in methylene blue solution under ultraviolet light and in the dark, in order to evaluate the adsorption of methylene blue in the samples. The analyses were performed to evaluate the concentration of methylene blue as a function of contact time. The concentration of the solution was monitored by spectroscopy in the visible ultraviolet spectrum. It turned out that the esmeraldine base was the material presenting a higher percentage of removal, 95.9 % after 96 hours of contact. The PAni(AA) samples showed a lower potential in the removal of dye. This suggests that azelaic acid occupies adsorption sites in PAni. The results also revealed that ultraviolet radiation influences the decrease in concentration of methylene blue, however, the tests in the dark indicate that the adsorption process predominates over photo degradation.
Keywords: Polianilina; Ácido Ázelaico; Fotodegradação; Polyaniline; Azelaic acid; Photodegradation; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA